AQUEOUS HUMOR CYTOKINE LEVELS AS BIOMARKERS OF DISEASE SEVERITY IN DIABETIC MACULAR EDEMA. Issue 4 (April 2017) - Hillier, Roxane J.; Ojaimi, Elvis; Wong, David T.; Mak, Michael Y. K.; Berger, Alan R.; Kohly, Radha P.; Kertes, Peter J.; Forooghian, Farzin; Boyd, Shelley R.; Eng, Kenneth; Altomare, Filiberto; Giavedoni, Louis R.; et al.
Abstract : Purpose: To determine whether aqueous cytokine levels correlate with disease severity in diabetic macular edema. Methods: A prospective cross-sectional study of 49 adults with diabetes mellitus, centre-involving diabetic macular edema and central subfield macular thickness ≥310 μ m on spectral domain optical coherence tomography. Clinical examination and aqueous sampling were carried out before an initial injection of ranibizumab. Multiplex immunoassay of sample was carried out for vascular endothelial growth factor, placental growth factor, transforming growth factor beta, intercellular adhesion molecule-1, interleukin (IL)-2, IL-3, IL-6, IL-8, IL-10, IL-17, vascular cell adhesion molecule-1, monocyte chemoattractant protein-1, and epidermal growth factor. Multivariate robust regression models were constructed, and adjusted for age, lens status, or severity of retinopathy, and size of foveal avascular zone. Results: Spectral domain optical coherence tomography macular volume was an excellent measure of disease severity, correlating strongly with central subfield macular thickness ( P < 0.001), best-corrected Snellen visual acuity ( P < 0.001), and baseline diabetic retinopathy severity ( P = 0.01). Elevated aqueous intercellular adhesion molecule-1 correlated with greater macular volume ( P = 0.002). No aqueous cytokine, including VEGF, correlated with central subfield macular thickness. There was an association between IL-10 levels and best-corrected Snellen visual acuity ( P = 0.03). Conclusion: Aqueous intercellular adhesion molecule-1 correlates with disease severity as measured by macular volume on spectral domain optical coherence tomography, and IL-10 is associated with BCVA. Intercellular adhesion molecule-1 may be a clinically useful biomarker for diabetic macular edema severity. Abstract : In treatment of naïve eyes with diabetic macular edema, elevated aqueous intercellular adhesion molecule-1 correlates with increased macular volume on spectral domain optical coherence tomography, and elevated aqueous interleukin-10 correlates with worse best-corrected visual acuity.